Race analyses among Winter Olympic sliding sports: A cross-sectional study of the 2018/2019 World Cups and World Championships - Williams, M. (Journal of Human Sport & Exercise, 2021)
Studies about the three Olympic sliding sports are sparse, little is known other than factors related to start performance. Therefore, this study aimed to add to the current literature by analysing the race characteristics of the nine different events. A non-experimental retrospective method was applied to analyse all races of the 2018/2019 season. A total of 3371 race trials sampled across the sports of bobsleigh (n = 1105), luge (n = 1401) and skeleton (n = 865). Split rankings were correlated to finish rankings using Pearson product-moment correlation to analyse the relationship of sectional rankings and race outcome throughout the race. The results exhibited sequentially increasing correlation coefficients in all events. Yet, there were distinctive characteristics differentiating the sports. Bobsleigh illustrated correlations coefficients that at a minimum were very large (r = .71) among all split rankings. Luge and skeleton depicted lower correlations for split 1 (r = .30 - .68) and thereafter substantially increasing as the race progressed. Thus, sliding performance can potentially have a greater impact in luge and skeleton than in bobsleigh. The differentiating race characteristics show the need for different training methods.